DEWAN KOMISARIS DAN PENGUNGKAPAN INFORMASI PENGENDALIAN INTERNAL - Fachry Rizqi Amin; Totok Dewayanto (Diponegoro Journal of Accounting, 2018)
This study aims to exmine the effect of boards commissioner size, independent commissioner, presence of women as independent variable and internal control information disclosure as dependent variable.            This study uses secondary data obtained from the Indonesia stock exchange (idx). This research using a sample as many as 324 manufacturing companies registered in BEI year 2014 – 2016. The methods used in this research is purposive sampling method. Statistical techniques used in this study is a multiple regression.            The results obtained from this research shows the board of commissioner size and independent commissioner, have a significant positive influence on internal control information disclosure. Presence of women have no significant result.